2011
DOI: 10.1080/10420150.2011.593034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma radiation on hard dental tissues of albino rats using scanning electron microscope – Part 1

Abstract: In the present study, 40 adult male albino rats were used to study the effect of gamma radiation on the hard dental tissues (enamel surface, dentinal tubules and the cementum surface). The rats were irradiated at 0.2, 0.5, 1.0, 2.0, 4.0 and 6.0 Gy gamma doses. The effects of irradiated hard dental tissues samples were investigated using a scanning electron microscope. For doses up to 0.5 Gy, there was no evidence of the existence of cracks on the enamel surface. With 1 Gy irradiation dose, cracks were clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In accordance with our results, El-Faramawy et al found total loss of the prismatic structure with porous areas of enamel irradiated with 6Gy gamma radiation [35]. Enamel irradiated with Nd:YAG laser (1.2 W power) developed glazed areas, cracks and craters Brazilian Archives of Biology and Technology.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, El-Faramawy et al found total loss of the prismatic structure with porous areas of enamel irradiated with 6Gy gamma radiation [35]. Enamel irradiated with Nd:YAG laser (1.2 W power) developed glazed areas, cracks and craters Brazilian Archives of Biology and Technology.…”
Section: Discussionsupporting
confidence: 92%
“…In the dose, range of 0.2-6.0 Gy, the impact of gamma radiation on the hard dental tissues (enamel surface, dentinal tubules, and cementum surface) was assessed using scanning electron microscopy for doses up 0.5 Gy. No signs of cracks on the enamel surface were observed, with a 1.0 Gy dose of irradiation, cracks were easily seen in specific locations, whereas with a 2.0 Gy dose, the enamel displayed morphological changes as disturbed prismatic and interprismatic areas (32) . Impact on the mechanical properties of dentin or enamel was observed for the radiation doses used in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…After radiation, osteoclasts may be more radioresistant than osteoblasts, potentially explaining why they predominate in cementum-related resorption sites and cells. Consequently, proportional increases in lytic activity and resorption sites have been previously observed [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 97%